Experimental Determination of Effective Minority Carrier Lifetime in HgCdTe Photovoltaic Detectors Using Optical and Electrical Methods - Haoyang Cui; Jialin Wang; Chaoqun Wang; Can Liu; Kaiyun Pi; Xiang Li; Yongpeng Xu; Zhong Tang (Advances in Condensed Matter Physics)
This paper presents experiment measurements of minority carrier lifetime using three different methods including modified open-circuit voltage decay (PIOCVD) method, small parallel resistance (SPR) method, and pulse recovery technique (PRT) on pn junction photodiode of the HgCdTe photodetector array. The measurements are done at the temperature of operation near 77 K. A saturation constant background light and a small resistance paralleled with the photodiode are used to minimize the influence of the effect of junction capacitance and resistance on the minority carrier lifetime extraction in the PIOCVD and SPR measurements, respectively. The minority carrier lifetime obtained using the two methods is distributed from 18 to 407 ns and from 0.7 to 110 ns for the different Cd compositions. The minority carrier lifetime extracted from the traditional PRT measurement is found in the range of 4 to 20 ns for x=0.231–0.4186. From the results, it can be concluded that the minority carrier lifetime becomes longer with the increase of Cd composition and the pixels dimensional area.